Freedom Is Not Enough: The War on Poverty and the Civil Rights Movement in Texas. - Watt, Alan J. (American Historical Review, 2012)
The article reviews the book "Freedom Is Not Enough: The War on Poverty and the Civil Rights Movement in Texas," by William S. Clayson.